Identification of AHSG gene polymorphism and association with flavor and odor compounds of Indonesian lamb meat - Septiyawan, Ganda Adi; Listyarini, Kasita; Noor, Ronny Rachman; Roosita, Katrin; Gunawan, Asep (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
Flavor and odor are important factors for consumers to consider the quality of lamb meat. The AHSG Alpha2-Heremans- Schmid Glycoprotein gene is associated with a fatty acid content and is indicated as a gene controlling flavor and odor compounds. The research aims to identify the AHSG gene polymorphism and its association with flavor and odor compounds in Indonesian lamb meat. The sample used in this study was 105 ram samples consisting of 10 Javanese Fat-Tailed Sheep (JFTS), 80 Javanese Thin-Tailed Sheep (JTTS), and 15 Jonggol sheep (JS). The AHSG gene polymorphism was validated using the PCR-RFLP technique with the EagI enzyme EagI. The association of the AHSG gene SNP (g.198655287 G>A) with odor and flavor was analyzed using the T-tests. The AHSG gene polymorphism in Indonesian lamb was polymorphic with three genotypes, i.e., GG, GA, and AA, and in the Hardy-Weinberg equilibrium. The AHSG significance was associated (P<0.05) with skatole compounds (MOA, EOA, MNA, and MI). The AA genotype is recommended for a candidate marker of flavors and odors because it associated with low compound values. The AHSG gene, specifically the SNP g.198655287 G>A, can potentially serve as a genetic marker for lamb meat production by reducing flavor and odor.